(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The study retrieves some of the main definitions of dramaturgy, understood as a principle that organizes the action according to the scene, whether performed by the dramatic author, director or scenic author, and aims to understand the relationships that are established during the process dramaturgical in the elaboration of the scenic action, beyond the dualistic and archaic notion that distinguishes dramatic text and staging. For this purpose, cases of narrative theater and witness theater, illustrative of the panorama of contemporary theatrical scriptures.